Serum Lactate Dehydrogenase 2 Isoenzyme as Marker of Bone Marrow Infiltration in Non Hodgkin Lymphoma - Mazher, Naghmana; Iqbal, Zafar; Aslam, Naumaan; Mazher, Seema (International Journal of Pathology, 2018)
Objective: To assess the level of serum lactate dehydrogenase 2 (LD2) in the patients of NHL with and withoutbone marrow infiltration.Introduction: Lactate Dehydrogenase (LDH) is commonly increased in patients with haemopoieticmalignancies and has been shown to be of prognostic value in patients with Non- Hodgkin lymphoma (NHL)especially. Serum LD2 isoenzyme level was determined in already diagnosed 60 patients of NHL.Aims and Objectives: Patients were divided into two groups, 30 patients with bone marrow infiltration (groupB) and remaining without infiltration (group C). The values were compared with 20 healthy age and sex matchedcontrtols (groupA). The estimations were made prior to the institution of chemotherapy.Results: LD2 level was significantly raised in NHL patients compared with controls. There was also significantdifference when the values were compared between the patients of NHL with and without bone marrow infiltration.The levels showed positive correlation with the extent of the disease.Conclusion: We conclude that the above mentioned non invasive parameter is useful indicator of the extent ofthe disease